System dynamics modeling for mitigating energy use and CO2 emissions of freight transport in Lebanon - Haddad, Marc (2019)
Lebanon's road transportation sector is one of the most unsustainable in the Middle East region due to the exclusive reliance on conventional engine vehicles for passenger mobility and freight. Previous studies showed that significant reductions in energy use and emissions can be achieved from combining mitigation strategies that improve engine technology for cars and increase the use of public transport. However, these are not sufficient to offset the growth in freight emissions, estimated to account for nearly half of total GHG emissions in 2040. Therefore, this study uses system dynamics modeling to estimate the potential reductions of fuel use and CO2 emissions from cleaner electrified truck technologies, combined with using electric rail for heavy freight transport. Modeling results showed potential reductions of 38% to 49% in 2040 compared to the baseline no-action scenario, depending on the share of electric light duty trucks. This can counter the significant growth trends from freight transport, as needed to transition the entire transportation sector in Lebanon to a more sustainable future.